2010
DOI: 10.1111/j.1365-2869.2010.00890.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disorders and work performance: findings from the 2008 National Sleep Foundation Sleep in America poll

Abstract: SUMMAR Y Chronic sleep deprivation is common among workers, and has been associated with negative work outcomes, including absenteeism and occupational accidents. The objective of the present study is to characterize reciprocal relationships between sleep and work. Specifically, we examined how sleep impacts work performance and how work affects sleep in individuals not at-risk for a sleep disorder; assessed work performance outcomes for individuals at-risk for sleep disorders, including insomnia, obstructive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
218
3
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 324 publications
(250 citation statements)
references
References 26 publications
14
218
3
5
Order By: Relevance
“…The negative impacts of sleep apnea and sleepiness on work performance are also being increasingly recognized. Multiple studies have also demonstrated that therapy of OSA is an extremely cost-effective use of health care resources (78)(79)(80).…”
Section: Sleep Disordersmentioning
confidence: 99%
“…The negative impacts of sleep apnea and sleepiness on work performance are also being increasingly recognized. Multiple studies have also demonstrated that therapy of OSA is an extremely cost-effective use of health care resources (78)(79)(80).…”
Section: Sleep Disordersmentioning
confidence: 99%
“…W krajach rozwiniętych z powodu szybkiego tempa życia i niedoboru snu u ponad 40% osób co najmniej kilka razy w miesiącu występuje nadmierna senność, istotnie wpływająca na funkcjonowanie w ciągu dnia. W badaniu wykonanym przez amerykańską Narodową Fundację Snu, oceniającym nasilenie senności Skalą senności Epworth w wybranej losowo grupie 1000 aktywnych zawodowo Amerykanów, nadmierną senność stwierdzono aż u 18% badanych [2]. Problem zaburzeń snu i nadmiernej senności jest szczególnie istotny u osób pracujących na zmianie nocnej, które poza następstwami wynikającymi z niedoboru snu dodatkowo doświadczają trudności wynikających z rozbieżności pomiędzy godzinami pracy i snu a wewnętrznym rytmem snu i czuwania, kontrolowanym przez zegar biologiczny.…”
Section: Case Descriptionunclassified
“…Involuntary episodes of sleep during working hours are more frequent on night shifts. It seems that the probability of making a mistake and causing an accident is even three times higher in the case of shift workers compared to people working in standard hours, and the risk is highest in the early morning when returning from work [12].…”
Section: Commentmentioning
confidence: 99%
See 2 more Smart Citations